Further insight into the neurobehavioral pattern of children carrying the 2p16.3 heterozygous deletion involving NRXN1: Report of five new cases. (26th August 2020) - Alfieri, Paolo; Scibelli, Francesco; Sinibaldi, Lorenzo; Valeri, Giovanni; Caciolo, Cristina; Novello, Roberta Lucia; Novelli, Antonio; Digilio, Maria Cristina; Tartaglia, Marco; Vicari, Stefano
Abstract: Increasing evidence links heterozygosity for NRXN1 gene deletions to a clinically wide spectrum of neurodevelopmental, psychiatric, and neurological disorders. However, to date, the neurocognitive and social communication features of children carrying this genomic rearrangement have not been assessed in detail. The cognitive and behavioral profiles of five children carrying a heterozygous NRXN1 deletion were investigated through systematic assessment of the cognitive and developmental levels, adaptive profile and presence of behavioral symptoms and autistic features. Furthermore, four transmitting parents were assessed by means of cognitive, psychopathological and parental stress tests. A below‐average cognitive level was documented in all children, and defective adaptive levels were observed in four of them. Three of the five children were diagnosed as having autism spectrum disorder in comorbidity with intellectual disability/global developmental delay, with a major impairment in social communication skills. The remaining two children presented with isolated intellectual disability and an unclassifiable neurodevelopmental disorder, respectively. This study provide data contributing to a more accurate characterization of the neurobehavioral phenotype of individuals carrying heterozygous NRXN1 deletions. This analysis indicates that these structural rearrangements are associated with a variable expression of neuropsychiatric symptoms, and cast some doubts about the incomplete penetrance of the disorder. Abstract : NRXN1 deletions are associated to heterogeneous neuropsychiatric disorders. Gene penetrance should be further explored.